Interpretation of the Concepts "Пул", "Деньги" and "Money" in Cognitive Linguistics - Anvarovna , Erdanova Sevara (Miasto Przyszłości, 2023)
The article deals with phraseological units and the proverbial fund, as well as aphoristic, since all these stable units conceptualize concepts that are significant for peoples, in particular, “money” that interests us. The material used in the work made it possible to see examples of how the idea of spiritual, ethical relations was reflected in the Russian, English and Uzbek fund of stable units and how the language means of expressing these categories were realized in the typical constructions of national stable units.